Pengaruh Potongan Harga, Pembayaran Non Tunai, dan Peningkatan Harga Jual pada Startup On Demand Terhadap Perolehan Laba Merchant - Reza, Laode Adi; Sulindawati, Ni Luh Gede Erni (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the effect of price discounts, non-cash payments, and an increase in selling prices on startup on demand to merchant profitability. This research is a quantitative study using primary and secondary data whose measurements use a Likert scale. Data Test Equipment used in this study is to test data quality consisting of validity and reliability tests. After that, it uses assumption testing consisting of normality test, multicollinearity test and heteroscedasticity test. Testing the hypothesis used is the T test, F test and the coefficient of determination. Data were analyzed by multiple linear regression analysis methods. The results of this study indicate that discounted prices, non-cash payments and increased selling prices have a positive and significant effect on merchantt profitability. In this case it means that price discounts, non-cash payments, and increased selling prices have an important role in merchant profitability